2012
DOI: 10.2319/031312-219.1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microcomputed tomography evaluation of rat alveolar bone and root resorption during orthodontic tooth movement

Abstract: Objective: To observe the real-time microarchitecture changes of the alveolar bone and root resorption during orthodontic treatment. Materials and Methods: A 10 g force was delivered to move the maxillary left first molars mesially in twenty 10-week-old rats for 14 days. The first molar and adjacent alveolar bone were scanned using in vivo microcomputed tomography at the following time points: days 0, 3, 7, and 14. Microarchitecture parameters, including bone volume fraction, structure model index, trabecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 20 publications
4
33
2
1
Order By: Relevance
“…Data were further reconstructed to provide axial cross-section images with SkyScan NRecon software (version 1.4.4; Bruker) and converted into 16-bit bitmapped TIFF images with a resolution of 1024 3 1024 pixels. 20 Tooth movement distance (D i ) (mm) was measured 3 times and averaged at each time point (i 5 0, 7, 14, 21, and 28 days). Tooth movement rate (V i ) was then calculated as V i 5ðD i À D iÀ1 Þ=7 (Fig 1, B).…”
Section: Methodsmentioning
confidence: 99%
“…Data were further reconstructed to provide axial cross-section images with SkyScan NRecon software (version 1.4.4; Bruker) and converted into 16-bit bitmapped TIFF images with a resolution of 1024 3 1024 pixels. 20 Tooth movement distance (D i ) (mm) was measured 3 times and averaged at each time point (i 5 0, 7, 14, 21, and 28 days). Tooth movement rate (V i ) was then calculated as V i 5ðD i À D iÀ1 Þ=7 (Fig 1, B).…”
Section: Methodsmentioning
confidence: 99%
“…Some previous studies on the effect of orthodontic treatment on changes in alveolar bone density have indicated that orthodontic tooth movement can decrease bone density around the teeth, 19,2123 whereas others have reported the opposite. 21,24,25 Campos et al 26 indicated that bone density around the teeth following orthodontic treatment is similar to that from before treatment.…”
Section: Introductionmentioning
confidence: 95%
“…21,24,25 Campos et al 26 indicated that bone density around the teeth following orthodontic treatment is similar to that from before treatment. Thus, research results regarding the effect of orthodontic treatment on bone density around the teeth have been inconsistent.…”
Section: Introductionmentioning
confidence: 97%
“…These data could also be utilized for further research in large animal and human models. Although in vivo lCT has been used in the assessment of bone remodeling in animal models [25][26][27], there are no reported studies from indexed literature about the real-time assessment of GBR in osseous defects with regard to volumes and mineral densities of newly formed bone (BVNFB, MDNFB) and remaining b-TCP particles (VRBP, MDRBP).…”
Section: Introductionmentioning
confidence: 99%